Twentieth-century Lutheran theologians - Mattes, Mark C. (Refo500 academic studies, 2013)
This collection of essays examines important twentieth-century Lutheran theologians, including European and North American voices. Each essay provides an overview of the life and thought of important confessional Lutherans who shaped theology with an ecumenical, world-wide impact. The focus here is not on later twentieth-century figures but earlier ones, selected similar to the spirit manifest in Karl Barth s contention "lest we forget where contemporary theology came from" (Protestant Theology From Rousseau to Ritschl). The essays composed over the last five years were initiated by Lutheran Quarterly in order to assess our recent past as we move into a new millennium. The goal of each author, each a leading theologian, has been to describe each thinker s life and vocation and how each thinker s work continues to impact theology today.